MAC3A and MAC3B, Two Core Subunits of the MOS4-Associated Complex, Positively Influence miRNA Biogenesis. Issue 2 (5th February 2018) - Li, Shengjun; Liu, Kan; Zhou, Bangjun; Li, Mu; Zhang, Shuxin; Zeng, Lirong; Zhang, Chi; Yu, Bin
Abstract : The MOS4-associated complex promotes miRNA accumulation by positively modulating pri-miRNA transcription, stability, and processing. Abstract: MAC3A and MAC3B are conserved U-box-containing proteins in eukaryotes. They are subunits of the MOS4-associated complex (MAC) that plays essential roles in plant immunity and development in Arabidopsis thaliana . However, their functional mechanisms remain elusive. Here, we show that Arabidopsis MAC3A and MAC3B act redundantly in microRNA (miRNA) biogenesis. Lack of both MAC3A and MAC3B in the mac3b mac3b double mutant reduces the accumulation of miRNAs, causing elevated transcript levels of miRNA targets. mac3a mac3b also decreases the levels of primary miRNA transcripts (pri-miRNAs). However, MAC3A and MAC3B do not affect the promoter activity of genes encoding miRNAs ( MIR genes), suggesting that they may not affect MIR transcription. This result, together with the fact that MAC3A associates with pri-miRNAs in vivo, indicates that MAC3A and MAC3B may stabilize pri-miRNAs. Furthermore, we find that MAC3A and MAC3B interact with the DCL1 complex that catalyzes miRNA maturation, promote DCL1 activity, and are required for the localization of HYL1, a component of the DCL1 complex. Besides MAC3A and MAC3B, two other MAC subunits, CDC5 and PRL1, also function in miRNA biogenesis. Based on these results, we propose that MAC functions as a complex to control miRNA levels through modulating pri-miRNA transcription, processing, and stability.